Changes in sirtuin 2 and sirtuin 3 mRNA expressions in rheumatoid arthritis - Kara, Murat; Yolbas, Servet; Sahin, Cem; Koca, Suleyman Serdar (Aves, 2017)
Objective: Sirtuins (SIRTs) play a prominent role in metabolism, apoptosis, aging, inflammation, and epigenetics. Inflammation, apoptosis, and epigenetics are pathogenic issues in rheumatoid arthritis (RA). This study aimed to evaluate SIRT2 and SIRT3 mRNA expressions in patients with RA. Material and Methods: Fifty-four patients with RA and 26 healthy controls were enrolled. Disease activity was determined using the disease activity score (DAS) 28-erythrocyte sedimentation rate (ESR) (score of > 2.6 was considered to be active). SIRT2 and SIRT3 mRNA expressions in the extracellular plasma were investigated by real-time PCR. Results: SIRT3 mRNA expression was higher in the RA group than in the healthy control group (4.64 fold, p< 0.001), whereas SIRT2 mRNA expression was relatively lower in the RA group than in the healthy control group (0.55 fold, p= 0.109). However, SIRT2 (1.73 fold, p= 0.065) and SIRT3 (3.58 fold, p= 0.051) mRNA expressions were relatively higher in patients with active RA than in those with inactive RA. Conclusion: In RA, SIRT3 mRNA expression is increased, whereas SIRT2 mRNA expression is decreased. Conversely, SIRT2 and SIRT3 mRNA expressions increase in active RA. Therefore, the fate of each SIRT may differ in RA.
Keywords: Rheumatoid arthritis; sirtuin 2; sirtuin 3